JNK‐IN‐8 treatment improves ARDS‐induced cognitive impairment by inhibiting JNK/NF‐κB‐mediated NLRP3 inflammasome - Yunchao Shi; Ying Fang; Peng Shen; He Liu; Longsheng Xu; Liyan Wang; Maoxian Yang (Brain and Behavior, 2023)
Abstract Purpose Cognitive impairment is a critical complication of acute respiratory distress syndrome (ARDS). However, effective interventions are lacking. Growing evidence demonstrates that c‐Jun N‐terminal kinase (JNK)‐mediated neuroinflammation is involved in the development of ARDS. Therefore, we hypothesized that the JNK pathway is involved in ARDS‐induced cognitive impairment. Methods An in vivo rat model of ARDS was established by treating it with lipopolysaccharide. The cognitive function was assessed by behavioral tests. The levels of pro‐inflammatory cytokines, JNK and NOD‐, LRR‐, and pyrin domain‐containing protein 3 (NLRP3) were analyzed by enzyme‐linked immunosorbent assay, western blot, or immunohistochemical analysis. Results We found that JNK inhibitor 8 (JNK‐IN‐8) alleviated cognitive impairment, neuroinflammation, and NLRP3 inflammasome activation in the ARDS rat model. Additionally, an in vivo study showed that the protective effect of JNK‐IN‐8 on cognitive impairment was blocked by nigericin, an NLRP3 activator. Conclusions Our data suggest that JNK‐IN‐8 treatment improves ARDS‐induced cognitive impairment by inhibiting the JNK/nuclear factor‐κB‐mediated NLRP3 inflammasome.